2013
DOI: 10.1111/jsm.12116
|View full text |Cite
|
Sign up to set email alerts
|

Oral Enclomiphene Citrate Stimulates the Endogenous Production of Testosterone and Sperm Counts in Men with Low Testosterone: Comparison with Testosterone Gel

Abstract: Introduction Clomiphene citrate is employed off-label in men who have low testosterone and for the restoration of sperm counts in men who have used exogenous testosterone. Clomiphene is a mixture of two diastereoisomers: zuclomiphene and enclomiphene. We evaluated enclomiphene citrate in men with secondary hypogonadism. Aim Our aim was to compare oral enclomiphene citrate as an alternative to topical testosterone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 33 publications
4
60
0
2
Order By: Relevance
“…Finally, CC represents a good alternative to TRT with the advantage of not blocking HPT axis, but taking into account our results and previous series (23, 25), it should be discussed with the patient that treatment will be permanent in most cases.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Finally, CC represents a good alternative to TRT with the advantage of not blocking HPT axis, but taking into account our results and previous series (23, 25), it should be discussed with the patient that treatment will be permanent in most cases.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, Kaminetsky and cols, and Wiehle and cols. reported that in patients with secondary hypogonadism who responded to EC therapy, once the treatment was stopped TT levels decreased and returned to the pre-treatment values (23, 25). Our results concur with the last two authors since all patients decreased TT levels 3 months after discontinuation of CC treatment, 78% of them under the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with sexual dysfunction and decreased fertility, cardiovascular and metabolic disorders, low bone mineral density, obesity, psychosocial and cognitive dysfunction among other chronic complications [2]. Four to five million men in the United States alone are testosterone (T) deficient [3], and about 20% of all infertility cases can be accounted for by the male factor, with an additional 30-40% which can be attributed to both male and female factors [4,5]. It has been projected that in years to come the Western world will face an increasing burden of male HG [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized study by Kaminetsky et al [21] , the investigators compared levels of testosterone, FSH, and LH after hypogonadal males used either oral enclomiphene citrate or testosterone gel. Twelve male subjects were assigned to either of the two treatments.…”
Section: Commentarymentioning
confidence: 99%